Toward Islamic Anthropology (American Journal of Islam and Society, 1986)
I. IntroductionA. The Science of AnthropologyThis study is speculative and concerns a difficult and complex subject.Its task is made more difficult as it defends a metaphysical position, advancesan ideological argument, and serves a moral cause. It will therefore remainan incomplete part of an on-going process in the debate on key issues in contemporaryMuslim society.The major task of anthropology' -the study of man-is to enable us tounderstand ourselves through understanding other cultures. Anthropologymakes us aware of the essential oneness of man and therefore allows us toappreciate each other. It is only quite recently in history that it has come tobe widely accepted that human beings are fundamentally alike; that they sharebasic interests, and so have certain common obligations to one another. Thisbelief is either explicit or implicit in most of the great world religions, butit is by no means acceptable today to many people even in "advanced" societies,and it would make no sense at all in many of the less-developed cultures.Among some of the indigenous tribes of Australia, a stranger who cannotprove that he is a kinsman, far from being welcomed hospitably, is regardedas a dangerous outsider and may be speared without compunction. Membersof the Lugbara tribe of northwestern Uganda used to think that all foreignerswere witches, dangerous, and scarcely human creatures who walked aboutupside-down and killed people by magic. The ancient Greeks believed thatall non-Hellenic peoples were barbarians and uncivilized savages whom itwould be quite inappropriate to treat as real people. Many citizens of modemstates today think of people of other races, nations, or cultures in ways notvery different from these, especially if their skin is differently colored or if ...